Performance Analysis of Maintenance Using the RAM Method (Reliability, Availability, Maintainability) on the Reciprocating Compressor Unit C-4xxx at PT PSX - Alief Anugrah; Rachmasari Pramita Wardhani; Bambang Sugeng (Jurnal Media Teknik dan Sistem Industri, 2026)
This study evaluates the maintenance performance of the Reciprocating Compressor C-4XXX unit, which plays a crucial role in the gas production process but frequently experiences disruptions such as unplanned shutdowns, high suction temperatures, and excessive exhaust pressure. The RAM (Reliability, Availability, Maintainability) method is used with historical data from January to November 2024. The research aims to analyze the maintenance performance of the Reciprocating Compressor C-4XXX, as well as to compile proposals for improving maintenance efficiency based on quantitative data and technical analysis using the RAM method, which is expected to provide insight for the management of company as a source of information on the application of the RAM method as a basis for efforts to optimize operations and improve machine performance. The methods used are quantitative analysis of the RAM method, Pareto diagram analysis, fishbone diagram, and 5W+1H improvement proposals. The results show an average Reliability (MTBF) value of 139.50 hours, MTTR of 1.66 hours, and Availability reaching 99.24%. Pareto analysis found the main cause of high temperature pressure disturbances, and Fishbone identified factors causing problems that occurred related to worker consistency, operating conditions, lubrication systems, cooling, and controls. Improvement proposals were prepared using the 5W + 1H analysis, covering aspects of labor, methods, machines, materials, and the environment taken from the fishbone analysis carried out. By using the RAM method for companies can contribute to improving technician competency, select quality components, and improving work procedures supported using information technology.